IMPLEMENTATION OF ALTMAN Z-SCORE IN PREDICTING PT BANK SUMUT'S SUSTAINABILITY - Simatupang, Eva Malina (Accounting and Business Journal; Vol 2 No 2 (2020): ACCOUNTING AND BUSINESS JOURNALDO - 10.54248/abj.v2i2.1001, 2020)
This research was conducted to determine and analyze the risk of bankruptcy of the company PT Bank SUMUT according to the Altman Z-Score. The population in this study is the financial statements of PT Bank SUMUT and the sample in this study is the financial statements of PT Bank SUMUT for 2017 - 2019. The type of data used is secondary data and the data collection techniques used are documentation from financial reports published through the www site. banksumut.co.id. The data processing technique uses the Altman Z-Score modification method. Based on the results of data processing, the 2017 Z-Score was 1.57; the year 2018 is 1.63 and the year 2019 is 1.19. Based on the results of data analysis, it can be concluded that PT Bank SUMUT is in a gray zone because the standard value is at 1.1 <Z-Score <2.6 and PT.